Efektivitas Penerapan ABA pada Siswa Autism Spectrum Disorder pada Siswa Kelas 1 SD Panca Budi Medan - Muhammad Rizky Fauzy; Dara Fitrah Dwi; Sukmawarti; Tiflatul Husna (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Autism Spectrum Disorder (ASD) is a developmental disorder that affects an individual's ability to communicate, socialize, and adjust to his or her environment. Children with ASD often face barriers to building social relationships and exhibiting contextual behaviors. One of the widely used approaches to address this challenge is the Applied Behavior Analysis (ABA) method, which focuses on reinforcing positive behaviors through learning principles. This study aims to determine the effectiveness of the ABA method in improving social skills and adaptive behavior of 1st grade ASD students of SD Panca Budi Medan. Through a descriptive qualitative approach, data is collected through observation, interviews, and documentation. The results of the study revealed that ABA interventions had a positive effect on improving communication skills, participation in social activities, and reducing negative behaviors in ASD students. In addition, the successful implementation of ABA depends on the active involvement of teachers in the learning process as well as parental support. The study also found obstacles such as limited parental understanding and lack of teacher training related to the ABA method. ABA is an effective method if it is carried out on an ongoing basis with collaborative support between schools and families.